2011
DOI: 10.1039/c0mb00262c
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic investigation of human Schistosoma mansoni infection

Abstract: Schistosomiasis is a parasitic infection that is endemic in many developing countries in the tropics and subtropics afflicting more than 207 million people primarily in rural areas. After malaria, it is the second most important parasitic infection in terms of socio-economic and public health. Investigation of the host-parasite interaction at the molecular level and identification of biomarkers of infection and infection-related morbidity would be of value for improved strategies for treatment and morbidity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 46 publications
(60 reference statements)
4
55
0
Order By: Relevance
“…Moreover, changes in human urinary biochemical profiles from areas where S. mansoni is endemic have been used to differentiate between infected and uninfected individuals. These findings were important in demonstrating possible changes in human liver function, gut microflora, and energy metabolism due to schistosome infection (260). However, the specificity of these metabo-lites was not assessed, so their use as accurate diagnostic markers has not been determined.…”
Section: Metabolic Markersmentioning
confidence: 99%
“…Moreover, changes in human urinary biochemical profiles from areas where S. mansoni is endemic have been used to differentiate between infected and uninfected individuals. These findings were important in demonstrating possible changes in human liver function, gut microflora, and energy metabolism due to schistosome infection (260). However, the specificity of these metabo-lites was not assessed, so their use as accurate diagnostic markers has not been determined.…”
Section: Metabolic Markersmentioning
confidence: 99%
“…Similar changes were also detected in infections by Fasciola hepatica, Necator americanus and other human helminth parasites [16]. Balog et al [17] had reported alterations in the gut microbial communities concomitant with S. mansoni on the basis of urinary response of rodent and human hosts. Li et al [14] could differentiate between infected and uninfected individuals with respect to Schistosoma infection by presence of twelve urinary and five faecal metabolites as biomarkers in infected individuals thereby supporting the hypothesis that S. mansoni alters the host gut microbial activity.…”
Section: Changes In Bacterial Populationmentioning
confidence: 59%
“…This alteration manifests itself by the presence of unsusual bacteria [40], greater proportion of common bacteria [40] or by presence of some metabolites in the faeces and/or urine [17]. These may be used as biomarkers for diagnosis of helminth infection that may be utilized for the humans and veterinary animals of economic importance.…”
Section: New Biomarkers Of Helminth Infectionmentioning
confidence: 99%
“…Experimental infections with single or multiple parasite species may allow the discovery of specific or common biomarkers, although they should be further validated in free living populations [15]. To this end, for example it has been shown by serum proteomics of Eimeria sp infected chickens that proteins usually not detected in the blood like those associated with mitochondrial metabolism are good candidates for time-course studies in coccidiosis.…”
Section: Predictive Candidates To Detect Parasitic Diseasesmentioning
confidence: 99%
“…Therefore, these could be considered as a source for novel diagnostic or prognostic biomarkers [15]. Nowadays, modern -omic technologies are offering high-throughput strategies for such a difficult system biology exploration, with the essential support of novel bioinformatic tools [24,25].…”
Section: Proteomic Platforms For the Identification Of Parasite Biomamentioning
confidence: 99%